Answer:
y + 1 = 3x
Explanation:
The graphed line is y = 3x - 1
The options given to us are
y + 1 = 3x
y = -3x + 1
y = 3x + 1
y - 3x = -3
Consider the first equation:
y + 1 = 3x
Substitute (0,-1) into the equation:
-1 + 1 = 3(0)
0=0
Substitute (1,2) into the equation:
2+1 = 3(1)
3 = 3
Thus the equation holds true for the given points.
Rearrange the equation
y + 1 = 3x
y = 3x - 1
As it is the same equation which was initially graphed, both of these lines will be same and overlap each other, resulting in infinite number of solution